Academic Achievement of Deaf and Hard-of-Hearing Students in an ASL/English Bilingual Program - Hrastinski, Iva (J Deaf Stud Deaf Educ, 2016)
There has been a scarcity of studies exploring the influence of students’ American Sign Language (ASL) proficiency on their academic achievement in ASL/English bilingual programs. The aim of this study was to determine the effects of ASL proficiency on reading comprehension skills and academic achievement of 85 deaf or hard-of-hearing signing students. Two subgroups, differing in ASL proficiency, were compared on the Northwest Evaluation Association Measures of Academic Progress and the reading comprehension subtest of the Stanford Achievement Test, 10th edition. Findings suggested that students highly proficient in ASL outperformed their less proficient peers in nationally standardized measures of reading comprehension, English language use, and mathematics. Moreover, a regression model consisting of 5 predictors including variables regarding education, hearing devices, and secondary disabilities as well as ASL proficiency and home language showed that ASL proficiency was the single variable significantly predicting results on all outcome measures. This study calls for a paradigm shift in thinking about deaf education by focusing on characteristics shared among successful deaf signing readers, specifically ASL fluency.